Fork elongation estimation in a motorcycle suspension via Kalman-filter techniques for semi-active end-stop avoidance control. Issue 1 (July 2017) - Colombo, T.; Delvecchio, D.; Savaresi, S.
Abstract: This paper is about the estimation of front suspension stroke in a motorcycle, oriented to the semi-active end-stop avoidance control. The proposed observer is based on a Kalman-filter that takes into account the external forces acting on suspension while the vehicle is turning or accelerating. Furthermore a practical state-reset strategy is proposed in order to improve estimation performances for wheelie manoeuvres and to limit the estimated state into suspension physical bounds. The experimental results show that the suspension position can be correctly estimated both on road and off-road driving conditions.